Effects of supercritical carbon dioxide‐ethanol cocoa butter addition in cocoa butter‐based salad dressings - Hussain, Norhayati; Maarof, Syahida; Mohamad, Roiaini; Rajentran, Komati; Umar, Nasiru Bilkisu (John Wiley and Sons, 2025)
Addition of cocoa butter containing phytosterols and antioxidants into food products can provide additional health benefit towards consumers. This work aimed to extract cocoa butter from cocoa beans using supercritical fluid extraction to formulate salad dressing containing blends of soybean oil and cocoa butter and compared it with commercial salad dressing. The most similar (insignificant different) characteristics as the control sample in terms of consistency index, flow index, apparent viscosity and crossover value were 10%–35% cocoa butter salad dressing (CBSD). In contrast, the 30% CBSD shows insignificant difference of emulsion stability compared to commercial salad dressing. The most desirable ratio of cocoa butter to be added into salad dressing was 30%. The findings may benefit the local cocoa and salad dressing producer on product diversification.